Human trafficking for criminal exploitation:: the failure to identify victims - Villacampa Estiarte, Carolina (European journal on criminal policy and research, 2017)
Human trafficking for criminal exploitation is one of the lesser-known forms of human trafficking. The failure of the criminal justice system to identify the victims of this type of trafficking can lead to a failure to take the victim-centred approach to trafficking espoused in the international legal instruments that regulate the matter, an approach that emphasises the protection of victims and respect for their rights. In light of earlier findings of the existence of unidentified victims of human trafficking for criminal exploitation in several European countries — the UK, Ireland, Spain, the Czech Republic and the Netherlands — a qualitative study was conducted, consisting of 37 in-depth interviews with practising criminal justice professionals and victim service providers in Spain. Because undetected victims of human trafficking for criminal exploitation are usually treated as offenders, the main aim of this research with professionals was to determine the causes of the criminal justice system’s failure to identify the victims of this specific form of trafficking in order to prevent them from remaining hidden victims.